2020
DOI: 10.1007/s10072-020-04940-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on neurological patients attending a botulinum toxin service

Abstract: Sir, On January 30, 2020, the World Health Organization (WHO) declared the emergence of a novel coronavirus (here named COVID-19), firstly reported few weeks earlier in Wuhan, Hubei Province of China, as a public health emergency of international concern. Since then, drastic countermeasures including shutdowns of public services have been implemented worldwide to reduce virus transmission: on March 9, 2020, the Italian Prime Minister imposed a national lockdown and ordered all hospitals to stop all non-urgent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 5 publications
1
15
0
1
Order By: Relevance
“…These results are supported by a recent study evaluating the effects of botulinumtoxin delay in patients with other pain conditions such as dystonia, spasticity, or hemifacial spasm, demonstrating the burden of neurological diseases during the lockdown [10]. Moreover, the botulinumtoxin delay in neurological patients has also been related to self-perceived worsening of their condition during the COVID-19 lockdown compared to controls [11]. In the same direction, our results demonstrate that onabotulinumtoxinA delay has also caused downside effects on patients with other chronic pain conditions such as chronic migraine.…”
Section: Discussionsupporting
confidence: 64%
“…These results are supported by a recent study evaluating the effects of botulinumtoxin delay in patients with other pain conditions such as dystonia, spasticity, or hemifacial spasm, demonstrating the burden of neurological diseases during the lockdown [10]. Moreover, the botulinumtoxin delay in neurological patients has also been related to self-perceived worsening of their condition during the COVID-19 lockdown compared to controls [11]. In the same direction, our results demonstrate that onabotulinumtoxinA delay has also caused downside effects on patients with other chronic pain conditions such as chronic migraine.…”
Section: Discussionsupporting
confidence: 64%
“…However, there are many possibilities for exercising at home during a quarantine. The WHO has declared the emergency of COVID-19 on January 30, 2020 [55], and due to the impact of this pandemic on social life and mental health, we suggest that doing a bit of physical exercise is better than doing nothing.…”
Section: Physical Exercise Effects On Anxiety and Depressionmentioning
confidence: 84%
“…Erro et al [ 18 ] carried out a case-control study about the effects of the BT outpatient clinic interruption on spastic patients and their health-related quality of life (HRQoL). Soon after the beginning of lockdown’s countermeasures in Italy, 137 patients (94 cases and 43 controls) were asked to rate their perceived worsening from the time of their last treatment using a visual analog scale and a standardized, two-component tool to evaluate their health status.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the case group reported a mean delay of therapy of about 73 days and a remarkable worsening of their condition than the control group (5.16 ± 3.09 vs 1.83 ± 3.34). Anyway, although the pandemic had important clinical consequences on neurological patients who suspended BT therapy, this evidence was not mirrored by a negative effect on HRQoL [ 18 ].…”
Section: Discussionmentioning
confidence: 99%